Engineering insects from the endosymbiont out. Issue 1 (January 2022) - Elston, Katherine M.; Leonard, Sean P.; Geng, Peng; Bialik, Sarah B.; Robinson, Elizabeth; Barrick, Jeffrey E.
Abstract : Insects are an incredibly diverse group of animals with species that benefit and harm natural ecosystems, agriculture, and human health. Many insects have consequential associations with microbes: bacterial symbionts may be embedded in different insect tissues and cell types, inherited across insect generations, and required for insect survival and reproduction. Genetically engineering insect symbionts is key to understanding and harnessing these associations. We summarize different types of insect–bacteria relationships and review methods used to genetically modify endosymbiont and gut symbiont species. Finally, we discuss recent studies that use this approach to study symbioses, manipulate insect–microbe interactions, and influence insect biology. Further progress in insect symbiont engineering promises to solve societal challenges, ranging from controlling pests to protecting pollinator health. Highlights: Insects are diverse and integral members of natural ecosystems. Some are pests that harm human health and agriculture, while others have beneficial roles. Many insects have evolved associations with symbiotic bacteria that are far more intimate and persistent than our interactions with the human microbiome. Insect symbionts from taxonomically diverse bacterial groups have been cultured and genetically engineered using a variety of techniques. Genetically engineered symbionts have been used to study symbiosis, to prevent insects from vectoring pathogens, and to control their insect hosts. Emerging synthetic biology tools will make it possible to use this paratransgenesis approach for new applications in more insect species in the near future.